The psychological antecedents as a predictor towards the willingness to seek counselling among Lesbian, Gay, Bisexual and Transgender (LGBT) - Soh, Jo Yong; Wan Jaafar, Wan Marzuki (Malaysia Association of Research and Education for Educators, 2017)
Lesbian, Gay, Bisexual and Transgender (LGBT) is not a disorder by itself but LGBT individuals just like everyone else, they experience psychological illness. LGBT individuals may also encounter unique risks to their psychological health and well-being. This study attempted to investigate the relationships between the psychological factors (the overall psychological distress, the general feelings of distress, performance difficulties, somatic distress and the attitudes towards seeking professional psychological help) and the willingness to seek counselling among lesbian, gay, bisexual and transgender (LGBT) people. A total of 100 LGBT individuals participated in this study and four types of questionnaires were used which were the Demographic questionnaire, the Hopkins Symptom Checklist-21 (HSCL-21), the Attitudes towards Seeking Professional Psychological Help Scale-Short Form (ATSPPH-SF) and the Intention to Seek Counselling Inventory (ISCI). In Pearson correlation analysis, the overall psychological distress was found to have significant low positive correlation with the willingness to seek counselling (r=.245). It follows that the general feelings of distress (r=.251) and performance difficulties (r=.236) were also found to have low positive correlation with the willingness to seek counselling. On the other hand, somatic distress were found not to have significant positive correlation with the willingness to seek counselling. Furthermore, the attitudes towards seeking professional psychological help was found to have also low significant positive correlation with the willingness to seek counselling (r=.299). These variables underwent Simple Linear Regression and the attitudes towards seeking professional psychological help was the best predictors to the willingness to seek counselling among LGBT people. Finally, the conclusion and implication of the study are discussed.